2013
DOI: 10.18061/emr.v7i3-4.3732
|View full text |Cite
|
Sign up to set email alerts
|

The Harmonic Minor Scale Provides an Optimum Way of Reducing Average Melodic Interval Size, Consistent with Sad Affect Cues

Abstract: Small pitch movement is known to characterize sadness in speech prosody. Small melodic interval sizes have also been observed in nominally sad music -at least in the case of Western music. Starting with melodies in the major mode, a study is reported which examines the effect of different scale modifications on the average interval size. Compared with all other possible scale modifications, lowering the third and sixth scale tones from the major scale is shown to provide an optimum or near optimum way of reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 33 publications
2
38
0
2
Order By: Relevance
“…Schenker explained the stepwise filling-in of intervals between harmonic tones with the term Zug (linear progression), which is a form of prolongation (Forte & Gilbert, 1982). 3.Most interesting for the present study, transition probabilities depend on scale degrees relative to the tonic. As Huron and Davis (2012) showed in their Figure 2, which is the same as Figure 9.7 in Huron (2006), some scale-degree transitions are much more common than others. The most common transitions in major-key melodies are the falling steps from 5 to 4, 4 to 3, 3 to 2 and 2 to 1-consistent with points 1 and 2 above.…”
Section: Probability Distributions Of Major Melodiesmentioning
confidence: 60%
See 3 more Smart Citations
“…Schenker explained the stepwise filling-in of intervals between harmonic tones with the term Zug (linear progression), which is a form of prolongation (Forte & Gilbert, 1982). 3.Most interesting for the present study, transition probabilities depend on scale degrees relative to the tonic. As Huron and Davis (2012) showed in their Figure 2, which is the same as Figure 9.7 in Huron (2006), some scale-degree transitions are much more common than others. The most common transitions in major-key melodies are the falling steps from 5 to 4, 4 to 3, 3 to 2 and 2 to 1-consistent with points 1 and 2 above.…”
Section: Probability Distributions Of Major Melodiesmentioning
confidence: 60%
“…Evidently we have not, but things are moving in a promising direction. The contribution by Huron and Davis (2012) is a significant step towards a new explanation, and it also has interesting broader implications. In this extended commentary, I will present a new approach that builds upon their work.…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…However, there appear to be some qualitative aspects that are not learned statistically. Specifically, the association of both happy/sad and bright/dark with high/low (respectively) have been associated with ethological cues (Huron, 2015;Huron & Davis, 2013;Kraepelin, 1899Kraepelin, / 1990Morton, 1977). Studies have suggested that the association with bright/dark and high/low (respectively) may be an intrinsic characteristic of perception (e.g., Marks, Hammeal, & Bornstein, 1987).…”
Section: Resultsmentioning
confidence: 99%